THE STABILITY STUDIES OF MIXED HALIDE PEROVSKITE CH3NH3PbBrXI3-X THIN FILMS IN AMBIENT WITH AIR HUMIDITY 70% USING UV-VIS SPECTROSCOPY AND X-RAY DIFFRACTION - Bahtiar, Ayi; Habibie, Khairul (Spektra: Jurnal Fisika dan Aplikasinya, 2020)
Perovskite Solar Cells (PSC), with the efficiency of more than 22%, has shown promising prospects for the future of environmentally friendly technology. However, low stability on humidity is a major problem limiting the commercialization of PSC. The perovskite material commonly used as a perovskite solar-cell active material is methylammonium lead tri-iodide (CH3NH3PbI3 or MAPbI3) prepared with a mixture of methylammonium-iodide (MAI) and lead iodide (PbI2). Perovskite material MAPbI3 is hygroscopic and easily decomposed into its constituent material, thereby reducing the performance of the PSC. Meanwhile, perovskite methylammonium lead-bromide (MAPbBr3) has higher moisture stability than MAPbI3 because it has a cubic crystal structure that has high symmetry. However, the efficiency of solar cells using MAPbBr3 as active material is lower than that of MAPbI3, due to a higher bandgap (~2.2 eV) than that of MAPbI3 (~1.5 eV). Therefore the wavelength range of sunlight absorbed by MAPbBr3 is shorter. We have studied the effect of the ratio of Bromium ion (Br-) insertion into MAPbI3 perovskite, forming mixed perovskite halide MAPbBrxI3-x on the stability of thin perovskite films in ambient with air humidity 70%. The value of x is varied from x = 0, 0.25, 0.5, 0.75 and 3. We measured the evolution of UV-Vis spectra and XRD patterns of thin perovskite films. The MAPbBr3 perovskite film is the most stable in high air relative humidity (> 70%). While mixed perovskite films with x = 0.5 are more stable as compared to the other x values based on absorption spectra. The XRD results showed that the stability of mixed halide perovskite is decreased with the increasing of x value.